2010
DOI: 10.1021/bi101343p
|View full text |Cite
|
Sign up to set email alerts
|

The Proline/Arginine-Rich Domain Is a Major Determinant of Dynamin Self-Activation

Abstract: Dynamins induce membrane vesiculation during endocytosis and Golgi budding in a process that requires assembly-dependent GTPase activation. Brain-specific dynamin 1 has a lower propensity to self-assemble and self-activate than ubiquitously-expressed dynamin 2. Here we show that dynamin 3, which has important functions in neuronal synapses, shares the self-assembly and GTPase activation characteristics of dynamin 2. Analysis of dynamin hybrids and of dynamin 1/2 and 1/3 heteropolymers, reveals that concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…3e) indicates that dimerization specificity is controlled by a spatial combinatorial code. As predicted from this code, hetero-oligomers consisting of dynamin 1 and dynamin 2 are observed 35 . Several residues contributing to the apparent specificity are localized in the strongly conserved coil of dynamin, Drp1 and Dnm1 that follows α3.…”
Section: The Dynamin–dimer Interfacesupporting
confidence: 59%
“…3e) indicates that dimerization specificity is controlled by a spatial combinatorial code. As predicted from this code, hetero-oligomers consisting of dynamin 1 and dynamin 2 are observed 35 . Several residues contributing to the apparent specificity are localized in the strongly conserved coil of dynamin, Drp1 and Dnm1 that follows α3.…”
Section: The Dynamin–dimer Interfacesupporting
confidence: 59%
“…The GTPase activities of dynamins are stimulated by their self-assembly into rings and coils (26, 34, 36). Therefore, it seemed likely that the enhancement of Dyn2 polymerization by His 6 -Arc would be accompanied by an increase in Dyn2 GTPase activity.…”
Section: Resultsmentioning
confidence: 99%
“…This finding may simply reflect the fact that Dyn1 has a much lower intrinsic propensity to self-assemble than the other two forms of dynamin (26,36), suggesting that Arc is a less potent scaffold for dynamins than microtubules or liposomes, which have a much higher valency. However, the fact that Dyn1 is predominantly expressed in presynaptic terminals, whereas Arc is absent from presynaptic terminals and axons but, like Dyns 2 and 3, is abundantly expressed in dendrites (9), may point to a more specific reason for this selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies aimed at defining the size of the minimal dynamin assembly unit have yielded conflicting results. For example, our sedimentation equilibrium measurements in the analytical ultracentrifuge indicated that all three forms of dynamin exist predominantly as monomer-tetramer or monomer-dimer-tetramer equilibria in solutions containing 300 mM NaCl [32-34]. The R369W mutation did not significantly alter sedimentation behavior of Dyn2 [20].…”
Section: Resultsmentioning
confidence: 99%